Effect of Elevated Temperature on Residual Strength of Self Compacted Concrete - Paul, Snahashish; Rashid, Muhammad Harunur; Rahman, Md Anisur (Journal of Engineering Science, 2020)
Self Compacted Concrete (SCC) is a material used in the construction industry to ensure proper compaction of concrete without providing any external energy. In case of exposure of SCC to accidental fire, an assessment of its residual capacity is needed. This study covers the observation of residual compressive strength, tensile strength and modulus of elasticity of self compacted concrete under elevated temperatures (150, 300, 450, 600 and 800⁰C) and cooling conditions (air cooling and water quenching). The compressive strength increased at 150⁰C and decreased continuously after this temperature. However, tensile strength and modulus of elasticity decreased at elevated temperatures compared with ambient temperature. The compressive strength at ambient temperature (30⁰C) was 27.0 MPa, and it raised to 28.7 MPa at 150⁰C for air cooling and 27.8 MPa for water quenching. Journal of Engineering Science 11(2), 2020, 107-115